(untitled) (Journal of Guidance and Counselling Studies, 2023)
The study investigated the impact of flooding on families/ parents in Ogba/EgAbema/Ndoni Local Government Area in Rivers State. The study adopted survey research design and was guided by three research questions and hypotheses. A population of seven hundred families/parents were used for the study, while a sample of three hundred parents/families were drawn through purposive sampling technique for the study. Each of the ethnic groups that constituted the local government area was sampled as follows: Omoku town 80, Egbema 40, Ndoni 30, Egi 50, Usomini 50 and Igburu, 50. The instrument for data collection was a structured questionnaire prepared by the researchers and titled: ‘Impact of Flooding on Families/Parents Questionnaire’ with four sections. The instrument was validated by experts in Measurement and Evaluation and in Guidance and Counselling. Pearson Product Moment Correlation was used to test the reliability coefficient at 0.05 alpha level of significant. Mean and standard deviation were used to answer the research questions and t-test statistics was used to test the hypotheses.